Analysis of Interpersonal Skills of Kenduri Tradition in Indonesian History Learning in Senior High School 1 Boyolali - Muadz Assidiqi; Sariyatun Sariyatun; Hieronymus Purwanta; Hasna Nur Fadillah Ramadhani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe the kind of kenduri tradition as local culture with various contexts of life in the history learning material and then actualization of the interpersonal skills with kenduri tradition in the history learning process in high school 1 Boyolali, Boyolali regency, Central Java, Indonesia. This study is a qualitative study using a case study approach. The data was collected through interview and observation with a history teacher. The researcher also analyzed a history teacher lesson plans, work plan on 2021 year, and medium-term project plans on 2021-2024 years as the part of data triangulation. The data analyzed using interactive data analysis techniques consisted of three stages: data reduction, data display, and data conclusion. This study showed that the kind of kenduri tradition in history learning material is relevant to actualize students' interpersonal skills that it is approach and collaboration skills. This study implicates additional history learning materials to integrate kenduri tradition as one of local wisdom in Central Java that to be well-designed by considering needs students' interpersonal skills during the Covid-19 pandemic.